INTEGRATING ISLAMIC ETHICS AND CLINICAL SAFETY IN SUNNAH CUPPING THERAPY SERVICES - Andik Isdianto; Novariza Fitrianti; Abdul Hamid Arif; Wahyudi Widada (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Sunnah cupping therapy (al-hijamah) is a popular Islamic healing method practiced globally. Despite its spiritual roots, it poses clinical risks, including infections, vasovagal shock, and procedural inconsistencies, often due to non-sterile tools and untrained practitioners. This study aims to explore how Islamic ethical values—sincerity (ikhlas), trust (amanah), and halal compliance—can be integrated with clinical responsibilities such as sterilization protocols, informed consent, and therapist competency. A thematic qualitative literature review was conducted using Islamic jurisprudence, fatwas (DSN-MUI), WHO and Ministry of Health (Indonesia) guidelines from 2015–2025. Findings reveal that neglecting the maqashid sharia principle of hifzh an-nafs (protection of life) contradicts both Islamic ethics and medical safety. Sunnah cupping services rooted in both spiritual values and professional protocols are more trusted by Muslim patients and improve therapeutic legitimacy. This study highlights the urgent need for national SOPs, certified training, and the development of Islamic cupping clinics with integrated protocols. These clinics can serve as models of sharia-compliant, clinically responsible health services. The research offers practical recommendations for Islamic medical institutions and policy-makers in strengthening Islamic-based complementary therapies in modern healthcare systems.